ABSOLUTE CIVIL RIGHTS` CLASSIFICATION - Щербина, Богдан Сергійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article analyzes absolute civil rights, as well as their separate types, in order to classify them for further research. Methods: dialectical, logical methods of generalization, analysis. Results: the criteria were set and the classification of absolute civil rights was made. Absolute civil rights occupy a fundamental place in the structure of civil law both in Ukraine and in other countries. Their research is the basis and general theoretical foundation for the study of a range of personal non-property rights, property rights, hereditary rights. As Ukraine has embarked on a path to reform its national legislation, reforming it and bringing it into line with international standards makes it impossible to carry out scientific research without taking into account positions on world developments. the community. Concepts of absolute civil rights, their legal nature has always been the subject of scientific discussion. If we summarize the scientific positions that are expressed in the scientific literature, then we can distinguish the following signs of absolute rights: these rights are not subject to limitation (alienation); these rights are eternal, unchanging, super-state, their content does not depend on the will of the legislator; they are innate, unconditional, unchanged, and therefore inviolable for the authorities. This characteristic reflects the natural nature of the rights. In scientific literature, these rights are also traditionally defined as natural. Absolute civil rights in the science of civil law have a diverse classification. To do this, use a lot of criteria. In our opinion, each classification should have a certain meaning, both theoretical and practical. Absolute civil rights can be categorized according to many criteria. Most of the criteria for their division reflects one or another aspect of the legal nature of each absolute civil law, its specific attribute, and so on. Thus, in the term of validity of absolute rights can be term and perpetual, which is important for the possibility of their implementation, because the expiration of the term of the law causes its termination. Absolute civil rights may be related to a person (personal non-property rights) or to property (real rights). Absolute civil rights may be inalienable (personal non-proprietary rights of an individual and personal non-proprietary intellectual property rights), and may be passed on to other persons (real rights, property rights of intellectual property, with the exception of those stipulated by law as inalienable). Absolute civil rights are divided into those arising from the birth of an individual (in particular, the right to life, the right to respect for dignity and honor, the right to health care, etc.), and those acquired in the course of life, activities, etc. (in particular, the right to own property can be acquired both in accordance with the agreements, and in the case of the creation or processing of things, as well as for other grounds provided by law). The emergence of certain absolute civil rights may require legitimization by the state (real estate rights, intellectual property rights for an invention, trademark) by issuing the relevant legal document.